Karakteristik dan Potensi Pangan Fungsional Flakes dengan Perbandingan Tepung Keladi Alami (Xanthosoma sagittifolium) dan Termodifikasi Heat Moisture Treatment (HMT) - Dewi, Komang Manik Kumala; Wiadnyani, Anak Agung Istri Sri; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Flakes are instant cereal in the form of thin crumbs with a crunchy texture and rich in carbohydrates which are practical and nutritious. Generally, flakes are made from cereals. Utilization of cocoyam flour can be used as an alternative because it is rich in carbohydrates. The use of cocoyam flour requires a breakthrough to improved the characteristics and functional properties by utilizing heat moisture treatment (HMT) modified flour which can improved the nutritional value of flakes and its potential as a functional food. The design study used in this study was a completely randomized design (CRD) with 6 treatment levels: 100:0, 80:20, 60:40, 40:60, 20:80, 0:100. All treatments were repeated three times to obtain 18 experimental units. The data obtained was analyzed by Anova, and if there was a significant effect, it would be continued with DMRT. The results showed that the comparison of cocoyam flour and modified HMT in flakes had a significant effect (P<0,05) on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, crunch time, color content and hedonic test on color (L a b), aroma, taste and overall acceptance. Comparison of 60% cocoyam flour and 40% modified cocoyam flour had the best characteristics of flakes with criteria of water content 2.15%, ash content 1.80%, protein content 3.39%, fat content 17.21%, carbohydrate content 71.80%, crude fiber content 1.16%, crunch time 2.06 minutes, color content L* 51.93, a* 7.90, and b* 22.07, the color is liked slightly, the aroma is liked slightly, the texture is liked slightly and crunchy, the taste is liked slightly, and the potential as a functional food with resistant starch content and food fiber content are 3.80% and 4.53%.